2013
DOI: 10.3892/ijmm.2013.1599
|View full text |Cite
|
Sign up to set email alerts
|

Expression of selected genes involved in steroidogenesis in the course of enucleation-induced rat adrenal regeneration

Abstract: The enucleation-induced (EI) rapid proliferation of adrenocortical cells is followed by their differentiation, the degree of which may be characterized by the expression of genes directly and indirectly involved in steroid hormone biosynthesis. In this study, out of 30,000 transcripts of genes identified by means of Affymetrix Rat Gene 1.1 ST Array, we aimed to select genes (either up- or downregulated) involved in steroidogenesis in the course of enucleation-induced adrenal regeneration. On day 1, we found 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“…Expression of Cyp11b2 gene serves as a marker of the adrenal ZG. Following enucleation, by in situ hybridization, transcriptome analysis and QPCR, a marked decrease in Cyp11b2 gene expression levels were observed between days 2 and 20 of experiment [10,11,56]. As demonstrated in present study, similar pattern of expression was found for Vsnl1 and expression levels of both genes were positively correlated (almost strong positive correlation r = 0.68).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Expression of Cyp11b2 gene serves as a marker of the adrenal ZG. Following enucleation, by in situ hybridization, transcriptome analysis and QPCR, a marked decrease in Cyp11b2 gene expression levels were observed between days 2 and 20 of experiment [10,11,56]. As demonstrated in present study, similar pattern of expression was found for Vsnl1 and expression levels of both genes were positively correlated (almost strong positive correlation r = 0.68).…”
Section: Discussionsupporting
confidence: 86%
“…The applied methods were described earlier [1,2,[45][46][47][53][54][55][56]. From collected cells, samples of adrenal zones and from samples of entire adrenal glands, total RNA was extracted using TRI Reagent (Sigma) and, then, purified on columns (Rnasy Mini Kit, Qiagen).…”
Section: Rna Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the primers mentioned above, SYBR green detection system was applied as described earlier [56,57,61,62,63,64]. Every of 20 μL reaction mixtures contained 4 μL template cDNA, 0.5 µM of specific primer and a previously determined optimum MgCl 2 concentration (3.5 M for one reaction).…”
Section: Methodsmentioning
confidence: 99%